儒家之家庭倫理與生命倫理爭議: 回應恩格爾哈特教授幾點意見: Confucianism on Family Ethics and Ethical Issues: A Response to Professor T.H. Engelhardt - LEE, Shui Chuen (International Journal of Chinese & Comparative Philosophy of Medicine, 2013)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. In response to Engelhardt’s emphasis of the status of family in the bioethics and culture war, I would argue that Confucianism takes the family as the basic social ethical unit, which circumscribes not only the individual’s interpersonal responsibilities within the family, but also everyone’s social and political relations at large. Family is both the starting point and the end point of one’s life, hence we have responsibilities of filial piety to our parents and to nurture our children. Through mutual responsibilities, the family provides shelter, provisions, safety, loyalty, affection, and moral support for its members. Such an ethical family provides the best education and balanced character development for the child, which leads to a prosperous and fruitful life. Hence, it is more than just to give the family the legal status in a family member’s medical and bioethical decisions. Chinese traditional medical practice demands that physicians treat a patient and the patient’s family as relatives with great empathy and affection. The ideal is a Confucian doctor. Bioethical and medical decisions are determined within the family in a harmonious fashion and to the greatest benefit of the patient. DOWNLOAD HISTORY | This article has been downloaded 153 times in Digital Commons before migrating into this platform.